Characteristics of microcrystalline cellulose derived from oil palm trunk slabs and its potential for use as tablet diluent - Chutima Jantarat; Sirikanya Kaewpradit; Jiraporn Chingunpitak; Suthon Srivaro (Heliyon)
This work aimed to investigate the potential of cellulose extracted from oil palm trunk slabs (OPTS), residues from oil palm lumber processing for pharmaceutical tablets. Due to varying wood cell characteristics within the oil palm trunk which might affect the quality of the cellulose extracted from OPTS, the suitability of cellulose extracted from different positions within OPTS with respect to trunk height for tablet diluent was therefore explored in this work. OPTS from the trunk's bottom, middle, and top parts were collected. The vascular bundle and parenchyma tissue of each OPTS section were then mechanically separated and converted into powders. Cellulose was extracted from the powder and microcrystalline cellulose (MCC) was derived using acid hydrolysis. The powder and tablet compression properties of the MCC were then evaluated and compared with that of the commercial ones. MCC yields from both types of wood cells decreased from the bottom to the top of the trunk. MCC obtained from parenchyma tissue was more suitable for pharmaceutical tablets due to its finer texture and smaller particle size, and only parenchyma-derived MCC was used for further study; except MCC from the top part was ignored due to its relatively low MCC yield. Most of the parenchyma-derived MCC's properties obtained from the bottom part were greater than that of the middle part but slightly lower than that of the commercial MCC, Comprecel® M102. The study of tablet compression properties of the MCC revealed that the tablet prepared from the MCC of the bottom part met the general requirement for tablet manufacturing, indicating that it could be potentially used as tablet diluents.